The Relevance of Endeavors to God's Destiny (Analytical Study of Q.S. An-Najm Verses 39-42 in the Interpretation of Nurul Qur'an) - Rizal Ramdani; Pathur Rahman; Deddy Ilyas (Penerbit Hellow Pustaka, 2026)
This research is entitled